Behind the scenes of Norway’s role in the Second World War. The Norwegian-British tonnage agreement from 11th November 1939 - Siemianowski, Jordan (Folia Scandinavica Posnaniensia, 2010)
On the outbreak of the Second World War, Norway’s merchant marine was the fourth largest in the world with its gross register tonnage of 4,8 million. It played substantial role in the state economy as it generated more than one third of the national income in the balance of payments. Yet, the conflict put the Norwegian sea transport in a difficult situation as it dependent on the two warring nations, i.e. Great Britainand Hitler’s Third Reich. To make matters worse, any case of tipping the balance by the Norwegian fleet in a favour of any of the two belligerents might lead to the suspicion that Norwayhad departed from the policy of neutrality. Aware of its perplexing situation, the Norwegian government issued the Provisional decree on the regulation of the conditions of charter during the war, which effectively strengthened its control of the national merchant marine, thus laying sound foundation for a tonnage agreement withGreat Britain which was eventually signed on November 1939. On the strength of this agreement,Norway placed 150 tankers at the disposal of the allies and paved the way for further agreements of this kind.